a) Oblicz wartość wyrażenia 6x + 1:
c) Oblicz wartość wyrażenia x17 - x
dla x = -4
6.(-4) + 1 =
dla x = 3
dla x = 0
dla x = 7
dla x = -5
dla x = -2
b) Oblicz wartość wyrażenia 8 - X:
d) Oblicz wartość wyrażenia 6 - 3e
dla x = 10
dla x = 5
dla x = -1
dla x = -1
dla x =
< =
dla x=0


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

a) Oblicz wartość wyrażenia 6x + 1:

dla x = -4    -> -24+1=-23

dla x = 3    -> 18+1=19

dla x = 0    -> 0+=0

dla x = 7    -> 42+1=43

dla x = -5    -> -30+1=-29

dla x = -2    -> -12+1=-11

b) Oblicz wartość wyrażenia 8 - X:

dla x = -4    -> 8+4=12

dla x = 3    -> 8-3=5

dla x = 0    -> 8-0=0

dla x = 7    -> 8-7=1

dla x = -5    -> 8+5=13

dla x = -2    -> 8+2=10

c) Oblicz wartość wyrażenia x17 - x

dla x = 10    ->  170-10=160

dla x = 5    ->  85-5=80

dla x = -1    ->  -17+1=-16

dla x = 0    ->  0-0=0